AKREDITASI SEKOLAH ANTARA HARAPAN DAN KENYATAAN - Khusnah, Laila (JURNAL BIOSHELL, 2013)
The purpose of the writing is to know: 1) the essence of school accreditation, 2) the basic  implementation of school accreditation, 3) how far implementation of school accreditation. School accreditation do every fifth year, statutory of UU sisdiknas n0. 20 tahun 2003 BAB  XVI Bagian Kedua Pasal 60(1), the aims of accreditation to determine expedience program and unit of education in formail education and nonformal education at every step. Do accreditation based:1) Undang Undang No. 20 Tahun 2003 Pasal 60, 2) Peraturana Pemerintah No. 19 Tahun 2005 Pasal 86 & 87, dan 3). Surat Keputusan Mendiknas No. 87/U/2002. Aplication of accreditation oftentimes be “ghost” unearthly to school who unseriously in application of education. So, they are (teachers and founders institution) gave chapter and verse autentik through a short cut. There are paid someone to do procesing data, there are do automatic acting with overtime-work for days, and many data manipulation. Evaluation data, process teaching and learning, or infrastruktur and grease to assessor. So it is need solution for realize the aims of accreditation.Keywords: school accreditation, education